Attitude, barriers and facilitators to practice-based research: cross-sectional survey of hospital pharmacists in Saudi Arabia. Issue 1 (December 2016) - Sultana, Khizra; Al Jeraisy, Majed; Al Ammari, Maha; Patel, Rahul; Zaidi, Syed
Abstract Background Little is known about the perceived attitude, barriers and facilitators of Saudi Pharmacists about practice based research. We aimed to measure the attitude, barriers, and facilitators of Saudi hospital pharmacists towards pharmacy practice research. Method A cross-sectional survey of hospital pharmacists (n  = 216) working in King Abdulaziz Medical Cities in Central, Eastern and Western region hospitals was conducted during first week of September, 2013. The survey instrument comprised of six different sections that explored pharmacists previous participation in research, items regarding attitude, perception and willingness to participate, motivators, barriers, different areas of interest for doing research and patient demographics. Quantitative data collected was initially explored using frequency distribution, and descriptive analysis was carried out. Mann-Whitney U and independent samples t-test were used to explore the differences between the study variables. Results One hundred and eighty two pharmacists completed the survey yielding a response rate of 84 %. Fifty-nine percent of pharmacists have prior research experience. Pharmacists with research experience were more confident in reading and evaluating research papers (p  = 0.01), and designing a research study (p  = 0.001). Pharmacists with previous research experience were also more likely to participate in future research opportunities (p  = 0.004) and were confident in their research skills (p  = 0.003). No differences were observed about the perceived value of research, facilitators and barriers to participate in research, between pharmacists with prior research experience and pharmacists who have no prior experience to do research. Conclusion Pharmacists in this study were unanimous about the importance of research but showed considerable differences in their confidence to carry out research. There is a need to provide additional support to enable Saudi pharmacists in conducting practice based research.